Achieving successful and sustainable project delivery in Africa : how to implement effective and efficient project management practices and policies - Okereke, Chima, 1946- (New York : Productivity Press, 2020)
African nations have an underdeveloped industrial and economic base such as their water supply, electrical systems, roads, railways, etc. Massive funding is required to build each of these basic services to the levels of developed nations - funding they don't have. Many African countries rely on assistance from the government and global companies looking to invest or facilitate projects in the region. And for a variety of reasons, many of these projects fail or are inadequate to fulfil the needs of the nation. In order to facilitate their own economic development, African nations need to cultivate efficient project management practices and policies that will help them achieve their goal of sustainability. This book by a multidisciplinary project management consultant, contributes to the body of knowledge that each African country can attain and sustain economic development by suggesting how to eliminate and correct most causes of failures of projects in construction, water treatment, electricity and renewable energy. It suggests that they should also be able to obtain the sustainable harvesting of the benefits of project deliverables which have been planned for in order to implement the various aspects of their economic development. The suggestions in this book will make a difference in project delivery and are comprehensive enough to create a root-and-branch change which will affect the people involved in making decision on projects and their delivery. Thus, project management teams and their managers, organization decision makers, companies looking to invest in the region, and politicians who plan the economy have to understand the causes of unhelpful practices and what needs to be done in order to produce productive and effective delivery of long-term sustainable project. The principal goal of this book is to advise public and private companies, and international organizations conducting projects in Africa on how to prepare themselves, their businesses and enterprises to solve the problems that cause failure of projects and abandonment of project deliverables. The book also recommends the necessity for a commercial enterprise or government entity to prepare and develop its vision, mission, and strategic objects to constitute the basis of a business plan which should be implemented for successful operations. After first identifying various failed and abandoned projects in Nigeria, Ghana and South Africa, the author provides an analysis of why these projects failed or were abandoned. By using methodologies of Organizational Project Management (OPM), Project Portfolio Management (PPM) and project management techniques, he suggests a framework for project delivery which could be used as a foundational structure and platform that will address the problem and provide solutions for the achievement of successful and sustainable project delivery in Africa.
OCLC-licensed vendor bibliographic record.
Keywords: Project management -- Africa; Sustainable development reporting -- Africa; Infrastructure (Economics) -- Africa -- Planning; BUSINESS & ECONOMICS / Project Management; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Management